The Jack tales : told by R.M. Ward and his kindred in the Beech Mountain section of Western North Carolina and by other descendants of Council Harmon (1803-1896) elsewhere in the Southern Mountains ; with three tales from Wise County - Chase, Richard; local Ward, R. M.; (R. Monroe), 1875-1944.; Chase, Richard, 1904- (New York, 2003)
Includes bibliographical references.Presents retellings of eighteen folk tales from the mountain country of North Carolina, featuring Jack, an Americanized version of the fairy tale
hero.Jack in the giant's newground -- Jack and the bull -- Jack and the bean tree -- Jack and the robbers -- Jack and the North West Wind -- Jack and the varmints -- Big Jack and little Jack -- Sop doll! -- Jack and the king's girl -- Fill, bowl! Fill! -- Hardy hardhead -- Old Fire Dragaman --
Jack and the doctor's girl -- Cat 'n mouse! -- Jack and King Marock --
5.1
Keywords: Follett Library Resources -- 5-8; sears; Jack tales -- North Carolina; Jack tales -- Appalachian Region, Southern; North Carolina. -- sears; Appalachian Region. -- sears